تأثـير المساندة الاجتماعية لدى المرأة المصابة بسرطان الثدي - مهيدي نعيمة (كلية العلوم الاجتماعية, 2020)
ملخص الدراسة: هدفت الدراسة الى محاولة معرفة العالقة بين املساندة االجتماعية و تقبل املرض لدى مصابات بمرض السرطان .وذلكمن خالل االجابة عن التساؤل التالي: مامدى تأثير املساندة االجتماعية على تقبل املرض لدى املرأة املصابة بالسرطان ؟ ولتحقيق أهدافالدراسةاستخدمت الباحثةاملنهجالوصفي واستعمال استبيان كأداة لدراسة, تكونت من مقياس )املساندة االجتماعية( بعد التأكد من خصائص السيكومترية,و جرى التأكد منصدق االداة وثباتها .ولتحقيق الدراسةقامتالباحثةباختيار عينةمن النساء املريضات بالسرطان . وكشفتالدراسةتتحقق الفرضية االولى : أن املرأة التي تحظى باملساندة االجتماعية أكثر تقبال لممرض . :summary Study و تتحقق الفرضية الثانية: أن املرأة التي تفتقر لممساندة االجتماعية أقل تقبال لممرض . The study aimed to try to find out the relationship between social support and disease acceptance among women with cancer. And by answering the following question: What is the effect of social support on acceptance of disease in women with cancer? In order to achieve the objectives of the study, the researcher used the descriptive method and used a questionnaire as a study tool, which consisted of the (social support) scale after verifying the psychometric properties, and the validity and reliability of the tool was confirmed. To achieve the study, the researcher selected a sample of women patients with cancer. The study revealed the following results: The first hypothesis is fulfilled: Is a woman who receives social support more receptive to the disease? The second hypothesis is realized: Is a woman who lacks social support less receptive to the disease? The results showed a high score with 82 and 75 percent of women accepting the disease, and they are the women who receive social support. The study also revealed a low score of 33% for a patient who did not lack social support.
Keywords: السرطان؛المساندة الاجتماعية؛سرطان الثدي؛